2020
DOI: 10.1371/journal.pntd.0008507
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, parasitological and molecular profiles of Cutaneous Leishmaniasis and its associated factors among clinically suspected patients attending Borumeda Hospital, North-East Ethiopia

Abstract: Background Cutaneous leishmaniasis is one of the most neglected tropical diseases increasing in its public health importance. In Ethiopia over 28 million people are living at risk of infection. Method Institution based cross-sectional study was conducted at Borumeda Hospital from February to May 2019. A total 205 leishmaniasis suspected patients were included by systematic random sampling technique. Socio demographic characteristics were collected using pretested questionnaires. Parasitological investigation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
13
13
0
Order By: Relevance
“…Our study revealed that 62.6% of the suspected cases were males. This study was in line with studies done at Borumeda Hospital, northeast Ethiopia [18,20], at Gondar University Hospital northwest Ethiopia [19,21], and in Tigray rural communities northern Ethiopia [22].…”
Section: Discussionsupporting
confidence: 90%
“…Our study revealed that 62.6% of the suspected cases were males. This study was in line with studies done at Borumeda Hospital, northeast Ethiopia [18,20], at Gondar University Hospital northwest Ethiopia [19,21], and in Tigray rural communities northern Ethiopia [22].…”
Section: Discussionsupporting
confidence: 90%
“…However, L. tropica appears to be circulating in the study area, because the only patient with L. tropica lesion has not reported any travel history. Males (55%) outnumbered females, which is supported by other studies conducted in Iran, or overseas [30][31][32]. This may be in terms of their more exposure to the sand fly bites because of the type and time of their occupations and their less coverage, which makes males more prone to insect bites in general.…”
Section: Discussionsupporting
confidence: 60%
“…This may be in terms of their more exposure to the sand fly bites because of the type and time of their occupations and their less coverage, which makes males more prone to insect bites in general. Even though all age groups are affected by CL, but the disease was more prevalent in the age group 21-30 years (20%), because they spent more time outside as active workforce [7,31,32], and there was no patient under 1 year old. Corroborating with some other researches, which could be in terms of their complete coverage and staying mostly indoors, resulting in lesser contact with vectors, as well as the long latency of disease [4,31].…”
Section: Discussionmentioning
confidence: 99%
“…Leishmaniasis is one of the major neglected tropical diseases primarily affecting peoples who are found in low socio-economical status ( World health Organization, 2021 ). Cutaneous leishmaniasis is a common health problem and it is highly prevalent in the northern and southern highland areas of Ethiopia ( Seid et al, 2014 ; Bisetegn et al, 2020 ). Peoples' awareness and perception towards leishmaniasis have its own impact to prevent the disease in endemic areas ( Alidosti et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%